Religious factors predict support for genomic medicine more strongly than politics, education, or trust: A survey of 4,939 adults in the United States - DuBois, James M.; Chin, Eu Gene; Solomon, Erin D.; Harris, Jenine K.; Hill, Peter; Baldwin, Kari; Baker, Lauren L. (Frontiers in Genetics, 2025)
BackgroundReligious affiliation and attendance at services is associated with lower levels of support for some genomic activities, such as genetic testing. However, little is known about why or how religion shapes attitudes toward genomics.Materials and methodsWe conducted a cross-sectional survey with 4,939 participants representative of nine religious groups in the US (including atheist and agnostic). The survey examined (a) attitudes toward diverse activities associated with genomic medicine, (b) religious beliefs and practices, (c) control variables including trust in the healthcare system and knowledge of genetics, and (d) demographics. We examined differences between groups using an Analysis of Covariance (ANCOVA), and developed a regression model to identify significant predictors of support for genetic medicine.ResultsWhen controlling for demographic variables, only small attitudinal differences existed between religious groups, though substantial variability existed within groups. Only seven variables uniquely predicted attitudes toward genomic medicine: acceptance of evolution, support for promoting community health within their spiritual community, knowledge of genetics, more permissive attitudes toward reproduction and end of life care within their spiritual community, distrust in the healthcare system, political orientation, and frequency of volunteering (in descending order).DiscussionOur findings suggest that stereotyping based on religious affiliation is seriously misguided, and engagement with religious groups on genomic medicine must go beyond education and address moral issues and worldviews.